The black widow [compact disc, unabridged] - Silva, Daniel, 1960- (Silva, Daniel, 1960- Gabriel Allon series., 2016)
Art restorer, assassin, and spy Gabriel Allon finds himself poised to become the chief of Israel's secret intelligence service, but not before answering the French government's request to eliminate the person responsible for detonating a massive bomb in Paris.